Icing test capabilities at DGA Aero-engine Testing. (2016) - Jérôme, Emilie; Hervy, Franck; Maguis, Séverine
Since the 1960s, DGA Aero-engine Testing has built facilities to test and certify parts and equipment of aircraft and rotorcraft in icing conditions. For aerofoil or blade testing, a 2D test set-up has been developed. For engine tests, a free jet configuration is used. Until recently, the standard conditions for icing were associated with the presence of clouds composed of supercooled small droplets. Nevertheless, recent accidents and incidents have highlighted the danger of other icing conditions such as supercooled large drops (SLD), ice crystals and mixed phase which is composed of ice crystals and small droplets. So, current and future challenges include the ability to simulate these conditions. To generate droplets larger than 100 micrometres, a new atomiser has been developed and calibration methods have been modified in consequence. The next planned step is the generation of ice crystals and mixed phase.